Iowa Ornithologists' Union, Quarterly field report, spring 1985 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Bendorf, Carl J.et al (1985)
Quarterly field report compiled by Thomas H. Kent and Carl J. Bendorf for spring 1985. Includes sighting of a Curlew Sandpiper and a Trumpeter Swan and discussion of the quantity, quality, and methodology of reporting sightings. Epson - sheet feed